Adrenal Adenoma and Pheochromocytoma: Comparison of Multidetector CT Venous Enhancement Levels and Washout Characteristics. Issue 2 (March 2016) - Northcutt, Benjamin G.; Trakhtenbroit, Michael A.; Gomez, Erin N.; Fishman, Elliot K.; Johnson, Pamela T.
Abstract : Purpose: The aim of the study was to compare multidetector CT venous enhancement level and washout characteristics of adrenal adenoma and pheochromocytoma, with the goal of defining a venous enhancement level predictive of pheochromocytoma. Methods: Retrospective review of medical records between 2002 and 2012 was performed to identify adrenal masses measuring less than 4 cm. Inclusion criteria for adrenal adenomas was venous phase contrast-enhanced computed tomography (CT), confirmatory adrenal CT (precontrast ± washout), 1 to 2 years stability, and absence of clinical indicators of pheochromocytoma. All pathologically proven pheochromocytomas with venous phase CT imaging were evaluated. Nodule size and attenuation (venous ± precontrast, delayed) were recorded. Student t test analysis compared venous enhancement levels. Results: One hundred eighty-three subjects with 200 adenomas were compared with 22 subjects with 26 pheochromocytomas. The mean (SD) venous enhancement level for all adenomas (58 [26] Hounsfield units [HU]) and lipid-poor adenomas (76 [25]) was lower than that of pheochromocytomas (111 [38] HU, P < 0.01). No adenomas enhanced greater than 130 HU, compared with 38% (10/26) of the pheochromocytomas. A threshold of 130 HU to identify pheochromocytoma was 38% sensitive and 100% specific for pheochromocytoma. Of the 17 pheochromocytomas with washout imaging, rapid washout was identified in all (10/10, 100%) that enhanced greater than 130 HU on the venous phase, compared with 43% (3/7) that enhanced less than 130 HU. Conclusions: An indeterminate adrenal lesion that enhances greater than 130 HU on multidetector CT cannot be assumed to be an adenoma. Hypervascular pheochromocytoma (>130 HU) mimics adenoma washout pattern; absolute venous phase enhancement level must be considered.